2021
DOI: 10.1101/2021.10.27.466055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic analysis and in silico studies link spike Q675H mutation to SARS-CoV-2 adaptive evolution

Abstract: Genotype screening was implemented in Italy and showed a significant prevalence of new SARS-CoV-2 mutants carrying Q675H mutation, near the furin cleavage site of spike protein. Currently, this mutation, which is expressed on different SARS-CoV-2 lineages circulating worldwide, has not been thoughtfully investigated. Therefore, we performed phylogenetic and biocomputational analysis to better understand SARS-CoV-2 Q675H mutants’ evolutionary relationships with other circulating lineages and Q675H function in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Moreover, a persistent infection, particularly in an immunosuppressed patient, provides an environment for sustained viral evolution, which can result in the emergence of variants within the infected host 22,41 , and has been hypothesized as a potential source for novel variants of concern 22,41 . The Spike Q675H mutation, an adaptive mutation that has emerged independently in several SARS-CoV-2 lineages 32,33 , arose in a compartmentalized infection in one individual (who was immunocompromised) after just 9 days of infection. The emergence of a functionally advantageous mutation in the heart in a short period of time highlights the potential role of extrapulmonary reservoirs of SARS-CoV-2 in viral evolution within persistently infected hosts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a persistent infection, particularly in an immunosuppressed patient, provides an environment for sustained viral evolution, which can result in the emergence of variants within the infected host 22,41 , and has been hypothesized as a potential source for novel variants of concern 22,41 . The Spike Q675H mutation, an adaptive mutation that has emerged independently in several SARS-CoV-2 lineages 32,33 , arose in a compartmentalized infection in one individual (who was immunocompromised) after just 9 days of infection. The emergence of a functionally advantageous mutation in the heart in a short period of time highlights the potential role of extrapulmonary reservoirs of SARS-CoV-2 in viral evolution within persistently infected hosts.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether these variants have been observed in other studies; GISAID data revealed that one mutation, Spike (S) Q675H, has previously been observed, present at as much as 3% frequency worldwide (January 2021). This mutation was not circulating at the time that this subject contracted SARS-CoV-2, but has since emerged in multiple SARS-CoV-2 lineages, indicating convergent evolution 32,33 . This mutation falls directly upstream of the furin-cleavage site and is predicted to enhance viral entry 32,33 .…”
Section: Comparison Of Viral Genomic Features Within Subjectsmentioning
confidence: 98%
See 1 more Smart Citation